Upregulation of cyclooxygenase system and growth factors as plausable mechanism of antinuclerogenic activity of leaf of Piper betle Linn: a molecular insight - Majumdar, Biswajit; Sinha, Amar Kumar; Yadav, Shekhar Chandra; Niroula, Dilli Ram (Journal of Nobel Medical College, 2012)
Allylpyrocatechol, the active component obtained from ethanol extract of leaves of Piper betle Linn at a dose of 120mg/kg body weight was shown to be an antiulcerogenic agent. Allylpyrocatechol was isolated from PBE by column chromatographic separation followed by preparative TLC and tested in rat ulcer model. Histological studies reveal that damage in the mucosal epithelium was corrected and the disrupted epithelium (as seen in ulcer) reversed with the test compound. The cellular, molecular and biochemical factors underlying the healing of gastric ulcer, such as, growth factors (EGF, EGF-R, SMAD-4) and cyclooxygenases (COX-1 and COX-2) were observed to be up-regulated in presence of APC during healing process. All the data showed statistical significance (by one way ANOVA) when compared to the experimental control value. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7294 Journal of Nobel Medical College (2012), Vol.1 No.2 p.14-24